Operational sustainability of microfinance institutions in emerging economies: The role of institutional quality, technology, and macroeconomic conditions - Thang, Le Ngoc; Nguyen, Kim Thi Chung; Dao, Thi Ho Huong; Truong, Quoc Cuong; Nguyen, Minh Nhat (Edelweiss Applied Science and Technology, 2025)
This study examines the key determinants shaping operational sustainability in Vietnamese microfinance institutions (MFIs), which play a vital role in advancing financial inclusion for marginalized populations. A quantitative survey was conducted with 311 MFI professionals, including credit officers, compliance staff, and middle managers. Exploratory Factor Analysis (EFA) validated the construct reliability, and multiple regression analysis was used to assess the influence of governance, digital transformation, business model diversification, macroeconomic conditions, and cost management. Governance and compliance (β = 0.284) and digital transformation (β = 0.262) were the most significant predictors of sustainability, followed by diversification (β = 0.212) and macroeconomic factors (β = 0.163). Cost management (β = -0.062) had no significant effect. The model explains 65.9% of the variance, confirming the strategic role of institutional quality and innovation over traditional cost-cutting approaches. To achieve long-term resilience, MFIs should prioritize strengthening governance structures, investing in digital capabilities, and diversifying service offerings. Policymakers and development partners are encouraged to support enabling frameworks that foster responsible innovation and institutional maturity in the Vietnamese microfinance sector.